Study on the Algorithm for Real-time Interpolation of NURBS Curve and Simulation - Hui Jizhuang; Wei Fangsheng; Gao Kai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In the paper, In order to meet the needs of high-speed and high- accuracy computerized numerical control machining and guarantee the smooth running in the interpolation processing, A NURBS curve calculation based on adaptive acceleration and deceleration control of look-ahead s-shaped for the real-time interpolation is presented in this paper. The algorithm has merits such as higher position accuracy, short processing time, no variation and so on. Through dynamic path simulation and interpolation results analyses with MATLAB, the interpolation algorithm is proved to be correct and rational. Through actual machining by OPEN platform with VC++, the algorithm is proved to be real-time and practicable. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2482